2022
DOI: 10.1021/acsapm.1c01616
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Stable Carbazole-Derived Polyaniline for Pseudocapacitors

Abstract: Supercapacitor energy storage devices are well suited to meet the rigorous demands of future portable consumer electronics (PCEs) due to their high energy and power densities (i.e., longer battery-life and rapid charging, respectively) and superior operational lifetimes (10 times greater than lithium-ion batteries). To date, research efforts have been narrowly focused on improving the specific capacitance of these materials; however, emerging technologies are increasingly demanding competitive performance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Charge can be stored via Faradaic and non-Faradaic mechanisms in the modified electrodes, resulting in excellent specific capacitance and good electrochemical cycling stability. 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charge can be stored via Faradaic and non-Faradaic mechanisms in the modified electrodes, resulting in excellent specific capacitance and good electrochemical cycling stability. 11 …”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that cycling stability of pseudocapacitive processes can be enhanced by modification with carbon-based nanomaterials. Charge can be stored via Faradaic and non-Faradaic mechanisms in the modified electrodes, resulting in excellent specific capacitance and good electrochemical cycling stability …”
Section: Introductionmentioning
confidence: 99%
“…Our Early Career Forum authors are pushing the boundaries of applied polymer science with the discovery of new materials, new mechanisms, and new applications. Their contributions address urgent global challenges in clean air and water, diagnostic medicine, antimicrobials, reduced energy consumption, smart materials, , sustainable materials, and energy storage and generation. , Specifically, polymer membranes are an essential feature of filtration systems that provide our world with clean air that has low particulate content and lower CO 2 levels and clean water that is free of microbes and heavy metal contaminants. Responsive polymers pave the way for diagnostic medicine in which the polymer responds to indicate the presence of disease. Next-generation polymer lubricants and hydrophobic surfaces provide reduced friction for increased efficiency. Smart and sustainable materials, , which provide function in a circular platform, serve to address the global plastics problem.…”
mentioning
confidence: 99%
“…Smart and sustainable materials, , which provide function in a circular platform, serve to address the global plastics problem. Polymers for energy storage and generation offer metal-free alternatives, , reducing the need for mining and extraction of key elements.…”
mentioning
confidence: 99%
See 1 more Smart Citation